[PP.03.03]: INDIVIDUAL-SPECIFIC NON-INVASIVE BLOOD PRESSURE MEASUREMENT BASED ON THE GENERATION MECHANISMS OF KOROTKOFF SOUNDS. (June 2015) - Xiang, H.; Liu, Y.; Qin, Y.; Yu, M.
Abstract : Objective: The amplitude ratios for systolic blood pressure (SBP) and diastolic blood pressure (DBP) in oscillometric method are determined empirically, which scatter among the population of subjects. The objective of the present research is to develop an Individual-specific blood pressure measurement method based on Korotkoff sounds principle and evaluate its accuracy. Design and method: A blood pressure measurement method based on the generation mechanisms of Korotkoff sounds was proposed. The traditional Korotkoff sounds method determine the SBP and DBP according to the appearance and disappearance of Korotkoff sounds respectively. In previous studies the amplitude of the Korotkoff sounds was used to identify the first and last Korotkoff sounds. Unfortunately the amplitude of the Korotkoff sounds usually became faint when the cuff pressure close to SBP or DBP. In present research, the occurrence time of the Korotkoff sounds for each cardiac cycle under different cuff pressure was observed. The Korotkoff sounds was delayed as the cuff pressure increased, which could be utilized to distinguish the false Korotkoff sounds. To overcame the drawback of the traditional Korotkoff sounds method, in present research the Korotkoff sounds delay time was utilized to eliminate the noise and the interference. Results: A method and corresponding instrument for blood pressure measurement base on Korotkoff sounds have been established. The instrument was validated according to the AAMI SP10. The mean deviation for SBP and DBP is 0.73 mmHg and -0.30 mmHg. The standard deviation for SBP and DBP is 2.39 mmHg and 2.85 mmHg. The percentages for the deviation of 255 pairs of measurements within 5, 10, and 15 mmHg for SBP are 94.9%, 99.2%, 100%, respectively. The percentages for DBP are 94.1%, 99.6%, 100%, respectively. Conclusions: The blood pressure measurement method and corresponding instrument utilizing Korotkoff sound delay time have met the requirement of AAMI SP10. It is an objective individual-specific method for determining the SBP and DBP than oscillometric method. The utilizing of the time delay characteristic of Korotkoff sounds under different cuff pressure enhanced its accuracy and clinical applicability.